Comparative ontogenetic survey of the essential oil composition in Origanum vulgare L., and Origanum majorana L - Tahmasebi, Somayeh; Majd, Ahmad; Mehrafarin, Ali; Jonoubi, Parisa (Acta Biologica Szegediensis, 2016)
The aim of this study was to evaluate the influences of the different harvest stages on the value and components of the essential oil (EO) of wild oregano (Origanum vulgare L.) and European marjoram (Origanum majorana L.). Two species were collected during five stages of vegetative and reproductive growth period with four replications. The content of EO in the dried aerial parts was determined by hydro-distillation of herbs, and its constituents determined by gas chromatography (GC) and gas chromatography mass spectrometry (GC/MS). The analysis showed that the amount of EO in O. majorana was more than O. vulgare. The highest EO content for both species were obtained in the full flowering stage. 78 and 39 components were identified in the EO of O. vulgare and O. majorana, respectively. The main components were germacrene D, (trans)caryophyllene, terpinene-4-ol, and a-terpinene in the EO of O. vulgare, and terpinene-4-ol, y-terpinene, a-terpinene, and a-terpineol in the EO of O. majorana. In general, sesquiterpene compounds had maximum amounts in the EO of O. vulgare in five stages of growth, especially in the beginning of flowering stage. In contrast, monoterpene compounds had maximum value in the EO of O. majorana in the full flowering stage.